Textile Dyeing Effluents and Environment Concerns - A Review - Islam, MR; Mostafa, MG (Journal of Environmental Science and Natural Resources, 2019)
Textile dyeing effluent is considered as one of the most environmentally unfriendly industrial processes. The study aimed to review the different types of textile dyes use in the industrial processes and their contribution to environmental pollution in South Asian countries. The article was prepared to compile all present data from different journals and website on textile dyeing effluents characterization in South Asia. A wide variety of synthetic dyes like azo dye, vat, reactive dye, disperse dye, etc. widely used in the textile sector. The result showed that some physicochemical parameters of the dyeing effluents (COD, TDS and BOD) exceeded their standard limits. The industrial effluents are affecting the main devastation to the aquaculture, agriculture, ecology, environment, and public health since the development of textile dyeing industries in these countries. Now a day, its proper supervision and curative measures like removal system have become the furthermost thoughtful tasks all over the world and the developing and transition economies countries in particular. It is imperative to take immediate steps to reduce the environmental pollution due to discharge the untreated textile dye effluents. J. Environ. Sci. & Natural Resources, 11(1-2): 131-144 2018